(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
It was Swami Dayanand who with his military approach made Indian realize that they were heir of a splendid heritage. It was he who made them realize that they must be adhere to their own religion, must be proud of their own culture and must cultivate their own language. This burning patriotism of Swami Dayanand made Indian Nationalism more broad based and brought it nearer to common masses of India. Dayanand Saraswati was a personality of the highest order. He was that rare combination, a thinker of action with a genius of leadership. His aim was to rally India against the encroaching in roads of Christianity and Islam and to obtain defense for her own traditional line of thought as inspired by Vedas. During his times Dayanand Saraswati was confronted by variety of faiths which were destroying the national glory. The Christianity, the Islam and even the Hinduism presented many hurdles on his way to nationalism. With his two watch words ’Back to Vedas’ and India for the Indians Swami Dayanand desired that religion as well as the sovereignty of India ought to belong to Indians. He was the great saint who wanted to bring reform. In his opinion strong, honest and truthful men of high character could not remain political slaves for a long lime. He loved Indians and India and perhaps the secret cause of his birth was to serve this holy motherland India upto his last breath.Swami Dayanand Saraswati (1824-1883) was one of the great leaders of Indian renaissance. He was not only a reformer who initiated a powerful movement to regenerate India’s society and religion but also a progressive thinker. Man is a creature of circumstances, says Robert Owen, but great men by dint of hard work and determination can exploit circumstances to achieve their objects. Swami Dayanand was one such great man.Dayanand was born in 1824 in a small town called Morbi in the princely state of Kathiawarh in modern day Gujrat. His father Karshanji Lalji Tiwari was a wealthy Brahmin and a devotee of Lord Shiva. Dayanand was his eldest son. Dayanand’s parents had named him Moolshankar. Karshanji was a man of influence and prestige and held the position of revenue collector. Swami’s mother name is Yashodabai, who was a very polite and religious lady. His father was stern, unbending and orthodox and wanted his son to emulate him. But Dayanand did not inherit these qualities of his father. Dayanand was being educated on the conventional pattern and was not permitted to mix freely with children of his age, outward influences left hardly any impact on his personality.